A rapidly evolved domain, the SCML2 DNA-binding repeats, contributes to chromatin binding of mouse SCML2. Issue 2 (18th August 2018) - Maezawa, So; Alavattam, Kris G; Tatara, Mayu; Nagai, Rika; Barski, Artem; Namekawa, Satoshi H
Abstract: Genes involved in sexual reproduction diverge rapidly as a result of reproductive fitness. Here, we identify a novel protein domain in the germline-specific Polycomb protein SCML2 that is required for the establishment of unique gene expression programs after the mitosis-to-meiosis transition in spermatogenesis. We term this novel domain, which is comprised of rapidly evolved, DNA-binding repeat units of 28 amino acids, the SCML2 DNA-binding (SDB) repeats. These repeats are acquired in a specific subgroup of the rodent lineage, having been subjected to positive selection in the course of evolution. Mouse SCML2 has two DNA-binding domains: one is the SDB repeats and the other is an RNA-binding region, which is conserved in human SCML2. For the recruitment of SCML2 to target loci, the SDB repeats cooperate with the other functional domains of SCML2 to bind chromatin. The cooperative action of these domains enables SCML2 to sense DNA hypomethylation in an in vivo chromatin environment, thereby enabling SCML2 to bind to hypomethylated chromatin. We propose that the rapid evolution of SCML2 is due to reproductive adaptation, which has promoted species-specific gene expression programs in spermatogenesis. Abstract : Here, we identify a novel protein domain in the germline-specific Polycomb protein SCML2; because the domain is comprised of rapidly evolved DNA-binding repeats, it has been termed the SCML2 DNA-binding (SDB) repeats.